(untitled) (Research, Society and Development, 2020)
This research aims to investigate the possibilities and challenges of teachers of the 5th year of the elementary school in public schools at São José de Ribamar/Maranhão, referring to the use of Information and Communication Technologies (ICTs) in the classroom. Thus, in view of the importance of ICT usage in school spaces recognized by the Common National Curriculum Base (CNCB), which is currently the main guiding curricular document of education in Brazil, is that we have the intention of identifying how teachers deal with the presence of ICTs. Therefore, the methodology used was using bibliographic studies, studying the guiding curriculum document of Brazilian basic education (i.e., the CNCB approved in 2017), and a survey with 18 teachers of the public school system. From the research results, it can be understood that ICTs already characterize the daily life of contemporaneity and that it is not, and cannot be, different in the classroom. Moreover, there is a need for the government to offer better infrastructure conditions for schools, e.g., with the development of policies to encourage continued teacher training. However, it is necessary for teachers in the exercise of their profession to be researchers and autonomous in the search for knowledge, to update themselves, in front of ICTs in pedagogical practice.